Demokrasi Pendidikan Islam Perspektif Muhammad Natsir dan Relevansinya dengan Sistem Pendidikan Nasional - Ulumuddin, Ihya` (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2016)
The article discusses Muhammad Natsirâs concept of democracy of Islamic education. Assessing democracy and Islamic education is inevitably important particularly when the modern people deal with such densely complicated problems within their life as they will lose a control upon the values of humanism. Therefore, emphasizing the values of humanity in their appropriate place within educational realm (in this context is Islamic education) is unquestionably pivotal matter. The study finds that democracy of Islamic education in Natsirâs perspective can be noticeably observed in his notions on integral, harmonious and universal education. Moreover, the author would argue that Natsirâs perspective of democracy within educational sphere has found its significance to the contemporary Indonesiaâs national educational system. It can be visibly seen, among others, in efforts to inhabit and cultivate the values of democracy, which have been firmly itemized in the Act of National Educational System. In this context, Islamic educational institutions have also take part and put great priority in cultivating such values within their all formal educational levels.